2019
DOI: 10.1177/0049475519843781
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya-induced inflammatory myositis: a case report in India

Abstract: Chikungunya fever is a benign and self-limiting disease caused by an RNA virus belonging to genus alphavirus and transmitted by infected Aedes mosquitoes. However, a number of atypical presentations involving various systems have been reported. Among the neurological complications, encephalitis, myelitis, Guillain-Barre syndrome and optic neuritis are commonly seen. However, its presentation as isolated inflammatory myositis causing quadriplegia is extremely rare. We report a 35-year-old woman with quadriplegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…5,8 Dev et al (2019) reported a case of inflammatory myositis following chikungunya infection in 2019 in India. 8 Martins et al (2016) reported a case of a patient presenting with myositis and encephalitis post-CHIKV infection in Brazil. 5 However, this is the first case of antisynthetase syndrome post-chikungunya infection characterized in literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,8 Dev et al (2019) reported a case of inflammatory myositis following chikungunya infection in 2019 in India. 8 Martins et al (2016) reported a case of a patient presenting with myositis and encephalitis post-CHIKV infection in Brazil. 5 However, this is the first case of antisynthetase syndrome post-chikungunya infection characterized in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Dev et al (2019) reported a case of inflammatory myositis following chikungunya infection in 2019 in India 8 . Martins et al (2016) reported a case of a patient presenting with myositis and encephalitis post‐CHIKV infection in Brazil 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported muscle alteration in human specimens [55][56][57][58]60,61], although the presence of the virus is not always demonstrated. Table 1 illustrates cases of muscle ex vivo studies from infected human patients.…”
Section: Of 19mentioning
confidence: 95%
“…Other studies have also reported muscle alteration in human specimens [ 55 , 56 , 57 , 58 , 60 , 61 ], although the presence of the virus is not always demonstrated.…”
Section: Muscle Alterations and Arboviral Myotropism In Humansmentioning
confidence: 99%